2020
DOI: 10.21203/rs.3.rs-54238/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial Distribution and Modeling of Malnutrition Among Under-Five Children in Ethiopia

Abstract: Background Majority of this world is concerned by malnutrition. Ethiopia is one of the Sub Saharan Africancountries known by poverty, childhood diseases, high mortality and poor infrastructures and technology. The study aimed to examine differences within individuals and between clusters in nutritional status of under-five children and to identify socioeconomic factors using adequate nutrition of children in Ethiopia. Method: Data was obtained from Ethiopian 2019 Mini Demographic and Health Survey surveyed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 2 publications
(2 reference statements)
3
6
0
Order By: Relevance
“…The spatial distribution of underweight was also clustered across the region and varies within the zones in the specific region. The similar findings was reported by a study conducted in Ethiopia that has detected that the Afar and Somali regions were the hotspot areas for underweight [41]. But, the previous study has reported that Fanti Rasu zone of Afar region, Metekel zone and Assosa administrative zones of Benishangul-gumuz region were identified as cold spot area for underweight in children under-five [42].…”
Section: Discussionsupporting
confidence: 87%
“…The spatial distribution of underweight was also clustered across the region and varies within the zones in the specific region. The similar findings was reported by a study conducted in Ethiopia that has detected that the Afar and Somali regions were the hotspot areas for underweight [41]. But, the previous study has reported that Fanti Rasu zone of Afar region, Metekel zone and Assosa administrative zones of Benishangul-gumuz region were identified as cold spot area for underweight in children under-five [42].…”
Section: Discussionsupporting
confidence: 87%
“…But it was higher than studies conducted in Tanzania [56], in Kenya [54], in Ghana [57], and in Senegal [58]. This finding was also in line with studies conducted in different parts of Ethiopia previously [27]. This finding for wasting is lower when compared with studies conducted in Ethiopia [59], in Senegal [58], and Cameroon [55].…”
Section: Discussionsupporting
confidence: 84%
“…A study conducted previously reported that significant clustering of wasting across regions. Thus, Afar and Somali regions were identified as hot spot areas for wasting [27]. A study conducted on spatial clustering of stunting…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations